Osteogenic assessment of leukocyte platelet-rich fibrin and injectable platelet-rich fibrin in the human osteosarcoma MG - 63 cell line in chronic periodontitis patients: An in vitro study - A. Sheryl Dolly; Prem Blaisie Rajula; P. L. Ravi Shankar; S. Lochini; Mohamed Rashik; Sindhujaa Raja (Wolters Kluwer Medknow Publications, 2024)
Background: The burgeoning interest in implant and regenerative dental care has led to a notable upsurge in the utilization of regenerative modalities. The intent of the present investigation was to evaluate the osteogenic ability of two different concentrated platelet groups at various concentrations in the human osteosarcoma MG-63 cell line. Materials and Methods: Blood samples from 21 volunteers with chronic periodontitis were collected which were then centrifuged in accordance with the protocols of Choukroun et al. and Miron et al. to produce leukocyte- and platelet-rich fibrin (L-PRF) and injectable platelet-rich fibrin (I-PRF), respectively. Following MG-63 cell culture, the osteogenic ability of 0, 4%, and 20% concentrations of both L-PRF and I-PRF were determined using the real-time polymerase chain reaction assay. Results: The results showed that 20% I-PRF (1.52 ± 0.24) and 4% L-PRF (1.42 ± 0.37) had the highest amount of bone morphogenetic protein 2 and osteocalcin, respectively. Conclusion: I-PRF appears to promote the initial differentiation of cells.